OTME-7. Cancer - immune cell interactions drive transitions to mesenchymal-like state in glioblastoma. (5th July 2021) - Hara, Toshiro; Chanoch-Myers, Rony; Mathewson, Nathan; Myskiw, Chad; Atta, Lyla; Bussema, Lillian; Eichhorn, Stephen; Kinker, Gabriela; Rodman, Christopher; Gonzalez, Nicolas; Wakimoto, Hiroaki; Rozenblatt-Rosen, Orit; et al.
Abstract: Communication between cancer cells and immune cells is a key determinant of the glioblastoma ecosystem and its response to therapies, but remains poorly understood. Here we leveraged single-cell RNA-sequencing (scRNA-seq) of human samples and mouse models, deconvolution analysis of bulk specimen from The Cancer Genome Atlas (TCGA) and functional approaches, to dissect cellular cross-talks in glioblastoma. We demonstrate that macrophages induce a transition of glioblastoma cells into mesenchymal-like (MES-like) states. This effect is mediated, both in vitro and in vivo, by macrophage-derived Oncostatin M (OSM) and its cognate receptor OSMR on glioblastoma cells. We show that MES-like glioblastoma states are also associated with increased expression of a mesenchymal program in macrophages and with increased cytotoxicity of T cells, highlighting extensive alterations of the immune microenvironment with potential therapeutic implications.